Showering is associated with Mycobacterium avium complex lung disease: An observational study in Japanese women. Issue 3 (March 2020) - Uwamino, Yoshifumi; Nishimura, Tomoyasu; Sato, Yasunori; Tamizu, Eiko; Uno, Shunsuke; Mori, Masaaki; Fujiwara, Hiroshi; Kawabe, Hiroshi; Murata, Mitsuru; Hasegawa, Naoki
Abstract: Mycobacterium avium complex refers to a group of environmental bacteria which inhabit water and soil. Although Mycobacterium avium complex is capable of causing refractory lung infections, the risk factors for Mycobacterium avium complex lung disease are still unclear. This study aimed to determine the associations between Mycobacterium avium complex lung disease and soil or water exposure. Using questionnaires along with clinical data, we compared soil exposure, along with bathtub bathing and showering habits between 172 women with Mycobacterium avium complex lung disease and 339 women without Mycobacterium avium complex infection as controls. Showering was found to be independently associated with the presence of Mycobacterium avium complex lung disease (adjusted odds ratio 5.72, 95%, confidence interval 1.99 to 16.46). Although the mean age of the groups was different, an age-matched sub-analysis yielded similar results. These results indicate that showering may be a risk factor for Mycobacterium avium complex lung disease.